Peningkatan Kemampuan Passing Bawah Bola Voli melalui Pola Gerak Berpasangan - Muhammad Edwin Fitriyanto; Taufiq Hidayat; Sri Wicahyani; Mochmmad Ridwan (Departement of Mathematics Education, 2024)
The game of volleyball is nothing but a big ball game. One of the movements used in volleyball is the down pass. The background of this research was because students in the extracurricular volleyball ball at SDN Wiyung 1 453 Surabaya were less able to place the ball in the middle of their hands and different foot patterns. This requires students to have a poor level of accuracy. This research aims to improve volleyball passing ability using paired movement patterns. Paired movement patterns can increase the active role and participation of students in participating in lower passing volleyball lessons. This research uses quasi-experimental research, using a quantitative approach with a sample of 15 people. Data collection through field observations, interviews and pretest and posttest on students. Data analysis used the hypothesis test paired sample t-test and Ngain. Based on the research results, it was found that paired movement patterns could increase the ability of passing down at SDN Wiyung 1 453 Surabaya as evidenced by the increase in the class average from 63.6 with 20% of students completing to a class average of 80.7 with 86% of students completing. This can also be seen in the increase in bottom passing ability with paired movement patterns at SDN Wiyung 1 453 Surabaya which is shown by an N-Gain value of 0.44 which shows moderate criteria, which means there is a moderate increase in bottom passing ability with paired movement patterns. at SDN Wiyung 1 453 Surabaya.